The synergetic effect of nano-structures and silicon-substitution on the properties of hydroxyapatite scaffolds for bone regeneration. Issue 19 (26th April 2016) - Xia, Lunguo; Zhang, Na; Wang, Xiuhui; Zhou, Yuning; Mao, Lixia; Liu, Jiaqiang; Jiang, Xinquan; Zhang, Zhiyuan; Chang, Jiang; Lin, Kaili; Fang, Bing
Abstract : Control over the morphology and chemical composition of hydroxyapatite (HAp) bioceramic scaffolds is of great importance for their applications. Abstract : Control over the morphology and chemical composition of hydroxyapatite (HAp) bioceramic scaffolds is of great importance for their applications. In the present study, Si-substituted HAp bioceramic scaffolds with controllable morphologies (nanosheets and nanorods) were fabricated via hydrothermal treatment of calcium silicate scaffolds as precursors in NaH2 PO4 and Na3 PO4 aqueous solutions, respectively. Moreover, the effects of surface morphologies and Si substitution on cell attachment, proliferation, and osteogenic differentiation of rat bone marrow stromal cells (rBMSCs) were systematically investigated in vitro . The results showed that nano-topography surfaces could enhance cell attachment, cell proliferation, alkaline phosphatase (ALP) activity, and mRNA expression levels of collagen 1 (COL1), bone morphogenetic protein 2 (BMP-2), bone sialoprotein (BSP) and osteopontin (OPN). Moreover, the Si substitution could further promote cell proliferation and osteogenic differentiation, while Si-substituted bioceramics with a nanorod surface possessed the highest stimulatory effect. More importantly, the in vivo rat critical-sized calvarial defect model confirmed that HAp bioceramic scaffolds with nanosheet and nanorod surfaces showed definitive bone regeneration as compared with control HAp bioceramic scaffolds with a traditional smooth surface. Moreover, Si substitution could synergistically enhance bone regeneration and mineralization, while Si-substituted HAp bioceramic scaffolds with a nanorod surface achieved the best bone repair ability. The present study suggests that the modification of the surface morphology and Si substitution on the HAp bioceramic scaffold may be an effective synergistic strategy to improve its clinical performance.